The Impact of Adopting Green Manufacturing Strategies on Achieving Competitive Advantage: An Analytical Study at the General Company for Food Products/Abu Ghraib Dairy Factories (Al-Mansour Journal, 2026)
This research aimed to determine the impact of adopting green manufacturing strategies (reduction, reuse, remanufacturing, and recycling) on achieving competitive advantage, as measured by its dimensions (cost, quality, flexibility, and delivery), at the General Company for Food Products/Abu Ghraib Dairy Factories. The research employed adescriptive-analytical approach, utilizing a questionnaire with a five-point Likert scale. The questionnaire was distributed to a sample of (60) managers at the Abu Ghraib Dairy Factories. Data analysis was performed using the SPSS., V.26 statistical software to calculate means, standard deviations, Spearman's correlation coefficient, and simple linear regression.The results confirmed asignificant correlation between green manufacturing and competitive advantage at the studied factories. Furthermore, the results demonstrated asignificant impact of green manufacturing on competitive advantage, with the level of this impact increasing when both are present. One of the most prominent conclusions reached by the research is that green manufacturing, with its four strategies, plays an important role in enhancing and building the reputation of the organization and contributes to achieving a competitive advantage. Despite the company under study adopting green manufacturing strategies, it suffers from weakness in implementing some strategies such as recycling, and it must work hard to provide high-quality, environmentally friendly and safe green products for customers, which will ensure that it achieves a competitive advantage and gains customer satisfaction and loyalty.
Keywords: Strategies; green manufacturing; green products; competitive advantage; customer satisfaction